Assessing Teachers’ Perceptions of Ethno-Mathematics as a Pedagogical Approach in Mathematics Education in Nigeria (American Journal of Educational Leadership & Policy Studies, 2025)
This study investigates how mathematics teachers in South-west Nigeria’s secondary schools view the application of ethnomathematics as a teaching method. The study used a descriptive survey design and collected data from 300 mathematics teachers who were chosen from among the six states in the area using a multi-stage sampling procedure. Teacher’s Perception of Ethno-Mathematics (TPE), a validated instrument, was used to collect data. It looked at teachers’ perspectives, integration strategies, and difficulties applying ethnomathematical ideas. Both descriptive statistics (mean and standard deviation) and inferential statistics (correlation and t-tests) were used in the data analysis process. The results show that although ethnomathematics is generally viewed favourably by teachers (overall mean = 3.26), who see it as a means of improving student engagement and link mathematics to real-world experiences, its actual integration into classroom instruction is still limited (overall mean = 2.26). Lack of instructional resources, inadequate training, and inadequate curriculum support are major obstacles. While there was no discernible difference in the perceptions or difficulties faced by teachers in public and private schools, the study did find a significant difference in integration practices between teachers in urban and rural settings. In order to facilitate ethnomathematics’ successful implementation in Nigerian schools, the study suggests that education authorities give professional development top priority, supply the required teaching resources, and formally include ethnomathematics in the national curriculum.